3D buckling assessment of cylindrical steel silos of uniform thickness under seismic action. (October 2018) - Mehretehran, Alireza Moazezi; Maleki, Shervin
Abstract: This paper investigates the dynamic buckling behavior of steel silos subjected to horizontal base excitations. The elastic-plastic buckling resistance of three silos with different aspect ratios is estimated using Incremental Dynamic Analyses (IDA). Accordingly, the critical base shear, base moment and the peak ground acceleration (PGA) at the buckling instant are calculated. Moreover, the additional normal pressures induced from bulk solids on silo walls are evaluated and compared with those of Eurocode 8. The results obtained suggest that slender silos are more vulnerable to buckling failure, while squatter silos represent a considerably higher resistance under same seismic conditions. Graphical abstract: Highlights: Comprehensive non-linear time-history analyses of steel silos were conducted. The elephant's foot buckling failure under horizontal base excitation was explored. Critical base shear, base moment and PGA at buckling were calculated by an IDA study. Dynamic pressures induced from accelerated bulk solids on silo walls were evaluated. Slenderer silos were considerably more vulnerable to buckling under seismic action.